Impact of Microglia in Neurodevelopmental Disorders: A Review - K, Dr. Pushpalatha; Sanil Kumar, Devika; Daripelli, Sushma; Bagchi, Sovan; Vasanthi, Rajkumar Krishnan; Khedekar, Sumod; Joseph, Danti (Biomedical Sciences and Clinical Medicine, 2025)
Objective Microglia, immune cells that dwell in the brain, have essential functions in neurodevelopment and are responsible for synaptic pruning, neuronal circuit creation, and inflammatory responses. Disrupted microglial activity can contribute to conditions such as autism spectrum disorders, schizophrenia, and ADHD by impacting the health and connections of neurons through the production of pro-inflammatory cytokines. These cells, which arise during central nervous system (CNS) development and have the ability to regenerate themselves throughout an individual’s lifespan, display considerable functional variation. Microglia, which have traditionally been known for their immunological functions, also play a role in regulating neurodevelopmental processes such as programmed synaptogenesis, synaptic pruning and cell death. Recent genetic and preclinical research indicates that abnormalities in microglial activity can result in a range of neurological diseases, varying in intensity from moderate to severe. The critical function of microglia in the development of the CNS is determined by their interactions with neurons and other glial cells, that have an impact on the structure of synapses and on the formation of new neurons. This review aims to fill gaps in earlier research by examining the diverse nature of microglial cells and their crucial functions in the development of the nervous system. It specifically focuses on current discoveries related to the rearrangement of synapses, the regeneration of neurons, and the impact of environmental stimuli. Comprehending these interactions is essential for creating precise treatments for neurodevelopmental diseases, emphasizing the necessity for ongoing investigation into microglial processes and measures to reduce their negative impact on brain development.